A Hybrid Approach for Big Data File Storage Using Enhanced AES With MHT Algorithm in Cloud Environment - Sindhe Phani Kumar, R. Anandan, P. Swaminathan (International Journal of Advanced Science and Technology, 2020)
The phenomenon of big data refers to the processing of huge data over the large network of computer. On the big data the growth of the demand in accessing the storage, computation and communication with data are the major defects. A raising issue in emerging big data is cost minimization. The architecture of big data ranges over multiple machines and cluster which have sub system. Be that as it may, because of the trouble of dissecting such huge datasets, huge information presents one of kind difficulties of building and designing framework. In this paper, the framework structure rules that give a compelling explanatory of information gathering handling, framework association, and information scattering rehearses are specified. The standards exhibited get from the investigation of huge information issues from different government organizations. The possible gap and drawbacks in the technology are identified through this survey and to provide the efficient big data service through MHT and AES algorithm is provided in this algorithm for the better future. The fundamental of enormous information with Different from ordinary cloud administrations is huge information administrations is the tight coupling among information and calculation as calculation errands can be directed just if that specific information are accessible in the information base.